Uniform Extendibility of the Bergman Kernel for Generalized Minimal Balls - Jong-Do Park (Journal of Function Spaces)
We consider a class of convex domains which contains non-Reinhardt domains with nonsmooth boundary. We show that the domains of this class satisfy the condition Q.